2023
DOI: 10.1111/psj.12508
|View full text |Cite
|
Sign up to set email alerts
|

Theorizing reactive policy entrepreneurship: A case study of Swedish local emergency management

Abstract: In this article, we examine public policy change at the local level of governance in the aftermath of an extraordinary event. Using the case study of a Swedish municipality after the sweeping forest fire of 2014, we contend that policy entrepreneurship, like its market counterpart, may under certain conditions take on a wider range of behaviors that are not underpinned by the proactive quest for opportunities. Rather, a sense of urgency and necessity, professional norms, and some keen technical skills make for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 63 publications
0
2
0
Order By: Relevance
“…The article builds on (Petridou et al, 2023), who suggested a nuanced view of policy entrepreneurship based on entrepreneurs' motives, and the methodological contribution of Petridou and colleagues (2021), providing more rigour and precision in identifying policy entrepreneurs. Christopoulos and Ingold's (2011) use of positive Bonacich power/Beta centrality to structurally identify policy entrepreneurs is seminal in this regard.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The article builds on (Petridou et al, 2023), who suggested a nuanced view of policy entrepreneurship based on entrepreneurs' motives, and the methodological contribution of Petridou and colleagues (2021), providing more rigour and precision in identifying policy entrepreneurs. Christopoulos and Ingold's (2011) use of positive Bonacich power/Beta centrality to structurally identify policy entrepreneurs is seminal in this regard.…”
Section: Discussionmentioning
confidence: 99%
“…In this article, we challenge the notion that policy entrepreneurs must necessarily have a specific policy in mind as they work to affect change. Following Petridou (2023) and Petridou et al (2023), we posit that, similarly to market entrepreneurship, policy entrepreneurship may emerge not only through opportunity structures but also through conditions of necessity. In market entrepreneurship, the latter is regarded as entrepreneurship by necessity.…”
Section: Introductionmentioning
confidence: 99%